Scraping Therapy and Muscle Resistance Training in Patients with Neck Dysfunction - Yucheng DUAN; Guangping SHEN; Xinjian LI; Enming ZHANG; Zhenmin BAI; Anli WANG (康复学报)
Objective:To investigate the effect of muscle resistance training and scraping therapy on patients with neck dysfunction and evaluate the treatment effect and follow-up effect so as to research on the mechanism of neck dysfunction.Methods:Gave one time isometric muscle resistance training to subjects suffering from neck dysfunction in the resistance training group (n=15), one time scraping therapy to subjects in scraping group (n=15), and evaluated the neck function through the visual analogue scale (VAS), neck disability index (NDI) and range of motion (ROM) before the intervention, immediately after the intervention, on the 3rd day after the intervention.Results:Compared with the VAS before the intervention, there was a very significant decrease in VAS immediately after the intervention in scraping group (P<0.01) and resistance training group (P<0.05). Compared to the three indexes of subjects before the intervention, scraping group had significant improvement in VAS (P<0.01), NDI (P<0.01), ROMs in sagittal and horizontal planes (P<0.05) and resistance training group had marked improvement in NDI (P<0.05), ROMs in coronal plane (P<0.05) and horizontal plane (P<0.01) on 3rd day after the intervention. Except for pain improvements (P<0.05) on the 3rd day after the intervention, no significant difference was found in all other measurements between the scraping group and the resistance training group.Conclusion:The neck dysfunction and pain level could be markedly improved by the scraping therapy and muscle resistance training, and it is recommended that the frequency of the resistance training could be three times per week in order to make the healing effect longer and more stable.